Wireless and Satellite Systems : 9th International Conference, WiSATS 2017, Oxford, UK, September 14-15, 2017, Proceedings /: 9th International Conference, WiSATS 2017, Oxford, UK, September 14-15, 2017, Proceedings. (2018) - Unknown
No abstract available